Comparative efficacy and safety of anti-cryptosporidial agents: an in vitro study on nitazoxanide, halofuginone lactate, KDU731, and paromomycin against Cryptosporidium parvum - Whitta, Saffron T. G.; Lamont, Bridget; Suwanarusk, Rossarin; Russell, Bruce M.; Muhsin-Sharafaldine, Morad-Rémy (Frontiers in Microbiology, 2024)
This study evaluated the in vitro effectiveness of anti-cryptosporidial agents nitazoxanide, halofuginone, the pyrazolopyridine analog KDU731, and paromomycin (PMC) in combating the significant zoonotic pathogen Cryptosporidium parvum. The study utilized HCT-8 host cells to culture C. parvum and fluorescent microscopy/quantitative PCR (qPCR) for detecting parasitic growth. The efficacy of the compounds was assessed by calculating their inhibitory concentrations (IC) against the total growth of C. parvum at 48 h post-infection. The study further investigated the impact of these compounds on early parasitophorous vacuole (PV) formation, merozoite egress, host cell viability, and cell growth cycle. KDU731 displayed the most promising profile, with low nanomolar (102 nM ± 2.28) activity and negligible host cell toxicity. This study offers new insights into the relative efficacy and safety of various anti-cryptosporidial compounds, highlighting their stage-specific effects on C. parvum and the consequential impacts on host cells. Identifying safe and effective anti-cryptosporidial agents contributes significantly to the One Health approach, which emphasizes the importance of integrated strategies in controlling zoonotic diseases.